2007
DOI: 10.1016/j.niox.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cell surface protein disulphide isomerase and S-nitrosoglutathione during nitric oxide delivery

Abstract: This is an electronic version of an article published in Nitric Oxide, 16 (1). pp. 135-142., February 2007. The definitive publisher-authenticated version is available from the journal homepage at:http://www.sciencedirect.com/science/journal/10898603The WestminsterResearch online digital archive at the University of Westminster aims to make the research output of the University available to a wider audience. Copyright and Moral Rights remain with the authors and/or copyright owners. Users are permitted to down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…NO produced by endothelium acts on platelets to maintain them in a resting state. Exposure to NO results in a decreased number of free thiols on megakaryocyte and platelet surfaces 31 and S-nitrosylation of multiple platelet receptors including a IIb b 3 is observed following exposure to NO. 32 PDI undergoes S-nitrosylation following exposure to NO donors.…”
Section: S-nitrosylation Of Thiol Isomerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…NO produced by endothelium acts on platelets to maintain them in a resting state. Exposure to NO results in a decreased number of free thiols on megakaryocyte and platelet surfaces 31 and S-nitrosylation of multiple platelet receptors including a IIb b 3 is observed following exposure to NO. 32 PDI undergoes S-nitrosylation following exposure to NO donors.…”
Section: S-nitrosylation Of Thiol Isomerasesmentioning
confidence: 99%
“…Delivery of NO from an S-NO donor into cytosol is inhibited following knockdown of PDI in HEL cells. 13 Inhibition of PDI blocks the delivery of NO from the physiologic NO donor, S-nitrosoglutathione, into both megakaryocytes 31 and into platelets. 35 PDI-mediated transnitrosylation is proposed to occur via the delivery of NO into cell membranes in the form of N 2 O 3 .…”
Section: S-nitrosylation Of Thiol Isomerasesmentioning
confidence: 99%
“…The published scheme shows plausibly how a single enzyme turnover brings about NO release, but the mechanism of active site thiol regeneration, required to continue RSNO signalling, is not yet defined. Several studies have documented thiol oxidation within csPDI and loss of enzyme activity as a result of the interaction with RSNO (Zai et al, 1999;Root et al, 2004;Shah et al, 2007). Redox regeneration of csPDI may derive from both internal sources, via transmembrane oxidoreductases such as NAD(P)H oxidase, and/or from reducing equivalents present in blood plasma.…”
Section: Cell Surface Protein Disulphide Isomerase Promotes No Delivementioning
confidence: 99%
“…Recently it has been shown that most cells (including neurons) contain GSNO reductase activity (Jensen et al 1998;Shah et al 2007), one of the more interesting being protein disulfide isomerase (PDI) activity (Sliskovic et al 2005). Thus, neurons are likely to self-limit the levels of intracellular GSNO produced by exogenous NO administration, producing an apparent ''ceiling'' Next, neurons were perfused with 1 lM spermine NONOate for 5 min.…”
Section: Discussionmentioning
confidence: 99%